University Students’ Understanding of Intermolecular Forces: A Comparison of First & Third-Year Students - Achmad Arifun Billah; Devita Aliya Octavia; Febriana Hidayatus Sholihah; Muhammad Rafli Febriliyanto; Nisa Nur Aisyah; Nuril Hafidzatur Rohmah; Sri Mulyani Sugiarti Rahayu; Tania Adilla Salsabela; Mudzuna Quraisyah Basimin; Habiddin Habiddin (PT Ahan Group Publisher, 2025)
The study aims to analyze chemistry education students’ understanding of intermolecular forces more deeply in 2021 (third-year) and 2023 (first-year). This type of research is descriptive research, and the technique used to collect data is a test and interview. Students encountered difficulties connecting types of Intermolecular Forces (IMFs) and molecular examples. Students’ understanding of hydrogen bonding is higher than that of dipole-dipole, induced dipole, and London (dispersion) forces. This study implies that third-year chemistry education students demonstrated superior mastery of intermolecular forces than first-year students.